Enzyme‐Mediated Modification of Single‐Domain Antibodies for Imaging Modalities with Different Characteristics. (2nd December 2015) - Rashidian, Mohammad; Wang, Lu; Edens, Jerre G.; Jacobsen, Johanne T.; Hossain, Intekhab; Wang, Qifan; Victora, Gabriel D.; Vasdev, Neil; Ploegh, Hidde; Liang, Steven H.
Abstract: Antibodies are currently the fastest‐growing class of therapeutics. Although naked antibodies have proven valuable as pharmaceutical agents, they have some limitations, such as low tissue penetration and a long circulatory half‐life. They have been conjugated to toxic payloads, PEGs, or radioisotopes to increase and optimize their therapeutic efficacy. Although nonspecific conjugation is suitable for most in vitro applications, it has become evident that site specifically modified antibodies may have advantages for in vivo applications. Herein we describe a novel approach in which the antibody fragment is tagged with two handles: one for the introduction of a fluorophore or 18 F isotope, and the second for further modification of the fragment with a PEG moiety or a second antibody fragment to tune its circulatory half‐life or its avidity. Such constructs, which recognize Class II MHC products and CD11b, showed high avidity and specificity. They were used to image cancers and could detect small tumors.